Flexural and tensile behavior of kenaf fibre composite materials - Abdi, Behzad (2013)
This paper presents the behaviour of kenaf fibre-epoxy composite material subject to three-point bend and tensile loading. Because of the nature of kenaf fibres that have high water and resin absorption capability, the effect of drying process and compression process on flexural and tensile behaviour of kenaf fibre composite materials was studied. Different kenaf-epoxy laminates including wet kenaf-epoxy, dried kenaf-epoxy and dried and compressed kenaf epoxy were fabricated by using vacuum infusion process and compression. Stress-strain curve for tensile test and flexural stress-extension curve for three-point bending were plotted. As a result, it was found that by drying the kenaf fibres before laminating, the mechanical properties of laminate were improved, and by compressing the laminate after the vacuum infusion process, the excess absorbed resin from the laminate was removed and the mechanical properties of laminate were improved. These parameters have a big effect on the flexural and tensile behaviour of kenaf fibre composite materials.